Case Report: Doege–Potter syndrome: a giant solitary fibrous pleural tumor causing severe hypoglycemia - De Vico, Christelle; Tappero, Carlo; Fontana, Enzo; Lutz, Jon Andri; Rouiller, Benoît (Frontiers in Oncology, 2025)
Doege–Potter syndrome or non-islet cell tumor hypoglycemia (NICTH) is a rare entity usually due to a solitary fibrous tumor of the pleura (pSFT). The diagnosis of NICTH is challenging because of its non-specific clinical presentation and the rarity of pSFT. We present a case report of a 44-year-old woman diagnosed with NICTH to demonstrate the difficulty of establishing this diagnosis and the importance of preoperative preparation based on the characteristics of the lesion. We performed an embolization followed by an en bloc resection with diaphragmatic patch and lung wedge resection, and we subsequently reconstructed the diaphragm with Prolene mesh through a left hemiclamshell incision. The postoperative course was favorable, particularly the resolution of hypoglycemia, which was concordant with the diagnosis. Pathological examination revealed a pSFT with clean margins and no features of malignancy detected by immunohistochemistry. This case report highlights the fact that diagnosing Doege–Potter syndrome is not always easy and often takes time after the patient’s initial presentation, the importance of preoperative planning, and the benefits of preoperative embolization of the arterial feeder.